Patterns of intracranial hemorrhage in petrous temporal bone fracture - Asha'ari, Zamzil Amin; Raja Lope Ahmad, Raja Ahmad Al'konee; Ab Rahman, Jamalludin; Yusof, Rosnida Azura; Kamarudin, Norie Azilah (Elsevier, 2012)
OBJECTIVE: To study the relationship pattern of intracranial hemorrhage in cases of traumatic petrous temporal bone fracture. METHODS: All head injury cases admitted to the Emergency Department, Hospital Tengku Ampuan Afzan, Pahang, Malaysia in 2008 were assessed. Computerized tomography (CT) scan of the skull base was performed in indicated cases. Patients with a petrous temporal bone fracture were included in the study. Subsequent magnetic resonance imaging (MRI) was performed. Intracranial hemorrhages incidence, management and outcome were recorded. RESULTS: From 1421 cases of head injury, 49(3.4%) patients were diagnosed to have a petrous bone fracture from the CT scan. Only 46 cases underwent MRI scan and were included in this study. Of these, 36(78.3%) cases had associated intracranial hemorrhages (p<0.01). Intracranial hemorrhage was associated with the longitudinal types of petrous fracture (p<0.05). Subdural hematoma was the most prevalent type of bleed (55.6%). There was no association between the types of intracranial bleeding (extradural, subdural, subarachnoid or intracerebral hemorrhage) and the types of petrous bone fracture (longitudinal, oblique or transverse). The mortality rate was 17.4%. The mortality cases were associated with the presence of other skull bone fractures (p<0.05). CONCLUSIONS: Petrous fracture is significantly associated with intracranial hemorrhage. There was no association between the types of petrous fracture and the types of intracranial hemorrhages in our material.